Faktor-Faktor Yang Mempengaruhi Minat Ibu Untuk Pijat Bayi Secara Teratur Di Polindes Desa Karangwedoro Wilayah Kerja Puskesmas Turi Kabupaten Lamongan Tahun 2023 - barok, kustini kustini (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Infant massage therapy is very good for the growth and development of infants but knowledge of infant massage, not widely known by the public because they still committed to a traditional baby. baby massage. Methods: The purpose of this research is to find their mother about massage infants Regularly. Methods used ini research is analytic quantitative design cross sectional. Research carried out in Polindes Karangwedoro Turi Lamongan. Data collection was conducted over month September-Oktober 2023, the population of this research is out the baby morher and infant immunization visit 0-12 months of age Polindes Karangwedoro Turi Lamongan 180. With sample from people. Data collection using a questionaire. Analysis used univariat and bivariat was conducted by the test chi-square to provide links between independent and dependent variable Results The analysis univariat most of the mother had a passion to do a massage baby regularly in Polindes Karangwedoro Turi Lamongan with the percentage 63,5 %, more mothers who are knowledgeable good with the percentage 61,8 %, more mothers who berpendidikn high with the percentage 80,0 %, more mothers do not work with the percentage 51,8 %, more mothers who a multiparous mammal with the percentage 60,6 %, more mothers who got the information with the percentage 61,8 %.The analysis of mother bivariat knowledge about massage baby p value 0,011 ( p>0,05 ) ho denied, education p value 0,015 ( p>0,05 ) ho denied, job p value 0,018 ( p>0,05 ) ho denied, parity of p value 0,021 ( p>0,05 ) ho denied, information p value 0,011 ( p>0,05 ) ho denied. The conclusion of the studied: 5 variable, all variable have meaningful connections for interesting mother to baby massage regularly in Polindes Karangwedoro Turi Lamongan . Conclusion: Advice in this research is Polindes Karangwedoro Turi Lamongan more concerned about growth and the baby development by building an interest i especially do regularly. baby a massage.